2000
DOI: 10.1017/s0958067000020923
|View full text |Cite
|
Sign up to set email alerts
|

Germ line transformation of mammals by pronuclear microinjection

Abstract: 591Figure 2Development of pronuclei and microinjection of DNA into the mouse zygote. A and C, development of pronuclei (arrows), about 20 and 26 h post hCG-injection for superovulation; B, DNA-microinjection into the male pronucleus; D, pronuclei disappear before the first cell division.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…The experimental introduction of DNA (transgenes) into the germ line provides an opportunity to probe an organism’s response to foreign DNA (Rulicke and Hubscher, 2000), and has revealed that organisms use a variety of mechanisms to silence transgenes in the germ line (Birchler et al, 2003; Brodersen and Voinnet, 2006). Interestingly, some mutants that disrupt transgene silencing also de-silence endogenous genes, including self-replicating elements called transposons (Ketting et al, 1999; Tabara et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental introduction of DNA (transgenes) into the germ line provides an opportunity to probe an organism’s response to foreign DNA (Rulicke and Hubscher, 2000), and has revealed that organisms use a variety of mechanisms to silence transgenes in the germ line (Birchler et al, 2003; Brodersen and Voinnet, 2006). Interestingly, some mutants that disrupt transgene silencing also de-silence endogenous genes, including self-replicating elements called transposons (Ketting et al, 1999; Tabara et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of efficiency for getting a transgene positive animal was found to be about 46% by this method, which was higher than the conventional method of transgensis by pronuclear DNA injection method 10–20%, 4,5 but lower than the earlier method which used gene electroporation in the testis. 7 Although we found the overall transgenic efficiency for this method is 46% (positive animals from all constructs taken together), Bucsn2-IRES2-Egfp and Fetuin A-shRNA the efficiency (70%) was found to be higher (70%) and lower (32%), respectively than the average.…”
Section: Discussionmentioning
confidence: 56%
“…For instance, classical method of gene transfer involves microinjection of nucleic acids into fertilized eggs, typically yielding low success rate of ~10–20%. 4,5 Moreover, this technique is beyond reach of common researcher, largely due to technical complexities in adopting skills for micro manipulation of embryos. 4 This has caused a remarkable delay in functional interpretation of several newly found genes in tissue and age specific manner, limiting the pace of biological research.…”
Section: Introductionmentioning
confidence: 99%
“…The use of expression cassettes in mammals suffers from the difficulty of identifying key regulatory elements, such as enhancers or silencers, that are necessary for the correct expression of a transgene [6]. A related source of variability is that expression of the label is influenced by the DNA sequences that flank the inserted DNA, yet the site of integration into the genome differs between transgenic animals.…”
Section: Labeling Of Specific Neuronal Phenotypes—mus Musculus As a “mentioning
confidence: 99%